Integrasi Kearifan Lokal dalam Evaluasi Lahan bagi Budidaya Enbal (Manihot esculenta Crantz) pada Kaki Gunung Ar, Pulau Yut, Maluku Tenggara - Geogriani Anthonius; Conradus Ufie; Simson Liubana (Universitas Pattimura, 2021)
Cassava is a food and trade commodity in the Kei Islands, Maluku Province. Various aspects of the cultivation of this crop are determined by traditional knowledge held by farmers from generation to generation. This study aimed to: 1) describe the potential of local wisdom (traditional knowledge) about the land owned by the Ohoi Wasar community in the Kei Islands regarding the suitability of the coastal land management for ‘enbal’ (bitter cassava) cultivation; 2) integrate local knowledge about land belonging to the Ohoi Wasar indigenous people with FAO land evaluation (modern soil knowledge in land suitability evaluation) for sustainable cultivation of ‘enbal’ cassava. This research was carried out using a transect-based survey method that was participatory and goal-oriented, which focused on farmers who cultivate ‘enbal’ cassava and their fields on the coastal land in the footslope of Mount Ar. The results of the study were: 1) there was local-traditional wisdom of the Wasar community that was directly related to ‘enbal’ cultivation (ethnopedological system); firstly, the wisdom of determining land suitability for ‘enbal’ cassava cultivation (ie. hadoichr ngametan or black soil = Renzina, and hadoichr vuil or red soil = Cambisol Dystrict); secondly was the wisdom of determining the time/day of land clearing for ‘enbal’ gardens (slash-and-burn) and the planting time which was started in early May; in addition, there was a supporting wisdom in the diversity or reliance of local foods, namely the habit of harvesting and consuming